Source of Biomass Cooking Fuel Determines Pulmonary Response to Household Air Pollution - Sussan, Thomas E.; Ingole, Vijendra; Kim, Jung-Hyun; McCormick, Sarah; Negherbon, Jesse; Fallica, Jonathan; Akulian, Jason; Yarmus, Lonny; Feller-Kopman, David; Wills-Karp, Marsha; Horton, Maureen R.; Breysse, Patrick N.; et al. (American journal of respiratory cell and molecular biology, 2014)
Approximately 3 billion people-half the worldwide population-are exposed to extremely high concentrations of household air pollution due to the burning of biomass fuels on inefficient cookstoves, accounting for 4 million annual deaths globally. Yet, our understanding of the pulmonary responses to household air pollution exposure and the underlying molecular and cellular events is limited. The two most prevalent biomass fuels in India are wood and cow dung, and typical 24-hour mean particulate matter (PM) concentrations in homes that use these fuels are 300 to 5,000 μg/m(3). We dissected the mechanisms of pulmonary responses in mice after acute or subchronic exposure to wood or cow dung PM collected from rural Indian homes during biomass cooking. Acute exposures resulted in robust proinflammatory cytokine production, neutrophilic inflammation, airway resistance, and hyperresponsiveness, all of which were significantly higher in mice exposed to PM from cow dung. On the contrary, subchronic exposures induced eosinophilic inflammation, PM-specific antibody responses, and alveolar destruction that was highest in wood PM-exposed mice. To understand the molecular pathways that trigger biomass PM-induced inflammation, we exposed Toll-like receptor (TLR)2-, TLR3-, TLR4-, TLR5-, and IL-1R-deficient mice to PM and found that IL-1R, TLR4, and TLR2 are the predominant receptors that elicit inflammatory responses via MyD88 in mice exposed to wood or cow dung PM. In conclusion, this study demonstrates that subchronic exposure to PM collected from households burning biomass fuel elicits a persistent pulmonary inflammation largely through activation of TLR and IL-1R pathways, which could increase the risk for chronic respiratory diseases.